OS 28-06 BENEFICIAL EFFECTS OF A 12-WEEK YOGA-BASED LIFESTYLE INTERVENTION ON CARDIO-METABOLIC RISK FACTORS AND ADIPOKINES IN SUBJECTS WITH PRE-HYPERTENSION OR HYPERTENSION. (September 2016) - Yadav, Rashmi; Yadav, Raj Kumar; Khadgawat, Rajesh; Mehta, Nalin
Abstract : Objective: To study the effects of 12 week yoga-based lifestyle intervention on cardio-metabolic risk factors and adipocytokines in overweight/obese subjects with pre-hypertension [systolic blood pressure (SBP) 130–139 mmHg or diastolic blood pressure (DBP) 85–89 mmHg] or hypertension (HTN). Design and Method: This prospective, single arm, lifestyle intervention study was conducted in overweight/obese (body mass index; BMI 23-24.9/ ≥ 25 kg/m 2 ) subjects (n = 44), with pre-HTN or previously diagnosed HTN. The subjects underwent pre-tested yoga-based lifestyle intervention including asanas, pranayama, relaxation techniques, lectures, group support, nutrition awareness program and individualized advice under supervision for approx. 2 hrs each day for 2 week followed by continuation of the practices at home for next 10 week. Outcome measures included cardio-metabolic risk factors: SBP, DBP, weight, BMI, waist circumference (WC), hip circumference (HC), waist-hip ratio (WHR), fasting plasma glucose (FPG), serum lipid profile and adipocytokines (plasma leptin and adiponectin levels). These were assessed at baseline, after 2 weeks of intervention and at end of week 12. Results: The mean age of subjects was 40.3 ± 5.5 yrs; mean BMI was 32.1 ± 4.9 Kg/m 2, SBP/DBP was 135.5 ± 13.2/85.6 ± 8.7 mmHg respectively. After intervention, there was significant reduction in weight, BMI, SBP, DBP, WC, HC, WHR, total cholesterol, and triglycerides (p < 0.05) from baseline to week 12. Likewise, there was significant reduction in leptin from baseline to week 12, however changes in adiponectin were not statistically significant (Fig. 1). Further a strong significant positive correlation between the change in weight and the change in WC (r = 0.9; p < 0.01) & HC (r = 0.7; p < 0.01) followed by 12 weeks of intervention was seen. Conclusions: These findings suggest that yoga-based lifestyle intervention might serve as an important treatment modality in reducing the risk of cardiovascular disease through weight loss, reduction in blood pressure, cardio-metabolic risk factors and adipocytokines in subjects with pre- HTN or HTN.